Attitude and socio-demographic factors influencing on using social media responsibly among students at Faculty of Allied Health Sciences, University of Jaffna - Pirashanth, K.; Kamalarupan, L.; Sathees, S.; Janani, T. (University of Jaffna, 2022)
In the modern era, social media have a potential impact on the student community, and it is essential that every student uses the social media responsibly as future health professionals. Lack of social media literacy can result in unethical behaviors in their professionalism. The study aimed to assess attitude, practice and socio-demographic factors influencing on responsible use of social media. An institution-based descriptive cross-sectional study was conducted among Allied Health Sciences students at the University of Jaffna. A sample of 426 participants were randomly selected and the data were collected via a validated self- administered questionnaire through google forms. Collected data were analszed using Statistical Package of Social Sciences version 23. The responses were received from 411students. (response rate=96.47%). The majority of participants, (n=281, 68.4%) were in the age group of 23 – 25 years. The mean age was 24.00 (SD= 1.43). Participants were categorized into positive attitude (65.2%) and negative attitude (34.8%) by using a 50% pre-determined cut-off value. Age, study programme, and academic year were statistically significant (p < 0.05) on the level of attitude. A positive attitude of 73.7% and 72.5% were observed among the participants of age group 23 to 25 and 26 to 28 respectively, which was relatively higher compared to age group 20 to 22. The study revealed that, more than half of the total study participants had a positive attitude towards using social media responsibly (65.2%). In certain categories, more percentage of participants exhibited negative attitudes regarding the use of social media responsibly. Those categories were participants from the first academic year (47.7%), male students (38.1%), and age group 20-22 (82.0%). According to these findings, attention has to be given to further improving their attitude of them towards responsible use of social media.
Keywords: Attitudes; Social media